Asma, rinitis alergi dan ekzema di kalangan kanak-kanak sekolah, Kota Bharu: perubatan prevalens dan faktor-faktor risiko - Rasid, Mazidah Abdul; Ibrahim, Wan Pauzi Wan; Nasir, Ariffin (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2003)
The prevalence and severity of asthma is increasing in many developed countries . Following the ISAAC phase I prevalence study in 1995, the phase III study was to evaluate the change in prevalence of asthma and allergic diseases during the past 5 years. AIM: I) To determine the prevalence of asthma, eczema, and aiJergic rhinitis in Kota Bharu school children, and to examine time trends in the prevalence of asthma, eczema, and allergic rhininoconj unctivitis in Kota Bharu school children, ii) to examine the environmental risk factors in children with recent wheeze. METHODS: The international study of asthma and allergies in childhood (ISAAC) written questionnaire was administered to 6, 161 school children from March to August 2001. The respondents were parents of 6-8 year primary school children (n =3, 157), and secondary school children 12-15 years (n = 3,004). The ISAAC video questionnaire was shown to secondary school children the written questionnaire. The prevalence figures obtained were compared with those obtained in 1995. RESULTS: The prevalence of ever wheeze between 1995 and 200 I were not significantly different among primary school children (8.3% 1995; 6.9% 2001) and secondary school children (10.7% 1995; 12% 2001). There was also no significant difference in the prevalence of recent wheeze among primary (5.4% 1995, 4.3°/o 2001) or secondary school children (6.8% 1995, 5.7% 2001). The prevalence of night cough in thelast I2 months among primary school children was significantly lower in 2001 (I 7.5%) compared to 1995 (20.4%). However, among secondary school children the prevalence of night cough, was significantly higher in 200 J (8.3%) compared to 1995 (5.1 %). The prevalence ofrhinoconjunctivitis in the last 12 months was not significantly different between 1995 and 2001 among primary school children ( 4.6% 1995; 5o/o 200 1) and secondary school children (11% 1995; 14.8% 2001). The prevalence of itchy flexural rash was significantly higher in 2001 (17.6%) compared to 1995 (14%) among primary school children, but similar among secondary school children (12.1% 1995; 13.4% 2001). The significant risk factors for recent wheeze were frequent consumption of paracetamol in the last 12 months OR 1.6 ( 95% CI 1.2-2.2 p = .OOI), consumption of meat ~3 times per week OR 1.5 (95% Cl 1.2 - 1.9 p <.00 1 ), frequent passing of trucks through the street of the house OR 1.4 (95% CI 1.1 - 1.8 p =.003), consumption of milk ~3 times per week OR 1.3 (95% CI I .0- 1.8 p =.04), consumption of fruit ~3 times per week OR 0.8 (95°/o CI 0.6- 0.9 p =.02). CONCLUSION: Except for changes in the prevalence of night cough, the prevalence of wheeze was similar between 1995 and 200 I. In atopic diseases there was a significant increase in flexural itchy rash among primary school children.